2004
DOI: 10.1046/j.0269-8463.2004.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of drought and shade on three arid zone chenopod shrubs with contrasting distributions in relation to tree canopies

Abstract: Summary 1.Plants that grow beneath trees in arid systems may frequently experience both water and light limitation, although protection from high radiation loads during drought may compensate for a loss of productivity due to reduced light availability when water is plentiful. 2. We examined the effects of shading, during an imposed water deficit, on the carbon gain, stomatal conductance ( g s ) and shoot water potential ( Ψ s ) of seedlings of three shrubs: Atriplex vesicaria (Heward ex Benth.), a C 4 species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 53 publications
3
54
1
2
Order By: Relevance
“…Thus, under growing light conditions, net photosynthesis rate was similar or even higher in this treatment than in the most illuminated one. This is in agreement with results from other studies on Quercus species which reported higher photosynthesis rate at intermediate light intensities (Castro-Díez et al, 2006;Prider and Facelli, 2004;Valladares et al, 2000).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, under growing light conditions, net photosynthesis rate was similar or even higher in this treatment than in the most illuminated one. This is in agreement with results from other studies on Quercus species which reported higher photosynthesis rate at intermediate light intensities (Castro-Díez et al, 2006;Prider and Facelli, 2004;Valladares et al, 2000).…”
Section: Discussionsupporting
confidence: 83%
“…The validity of the three above-mentioned hypotheses will depend on the species, the intensity of water stress, the range of light studied, the traits considered and many other experimental features as seedling age or environmental conditions. The tolerance of the different species to the combined effect of drought and shade determines their distribution and regeneration niches (Prider and Facelli, 2004;Sack, 2004). The question addressed in this study is how does the early development of cork oak growing under moderate water deficit change across a light gradient.…”
Section: Introductionmentioning
confidence: 99%
“…The negative impact of drought on seedling growth and survival can be less in the shade than in high light (Sánchez-Gómez et al 2006). It has been suggested that, in dry environments, the negative impact of shade on light availability is more than compensated by the positive impact in reducing heat load and transpiration (Prider & Facelli 2004). The facilitative effects of shade have been documented as a crucial mechanism of regeneration in Mediterranean-type ecosystems (Maestre et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the impact of such interactions can help us to understand the adaptation of plants to different ecosystems and to develop the most appropriate forestation techniques to be used in fragile and extreme areas (Walters and Reich 1997). Therefore, investigations of the response of plants to combined drought and shade have gradually become a focus during recent years (Sack and Grubb 2002;Prider and Facelli 2004;Ashton et al 2006).…”
Section: Introductionmentioning
confidence: 99%